(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Even if current technologies are used in removal of a skull-base epidermoid cyst, the maintenance of function of the cranial nerves is still an important issue. Purpose: To assess changes in ophthalmological abnormalities after surgery for skull base epidermoid cysts. Material and Methods: We retrospectively reviewed the medical records of 21 patients who underwent surgery for epidermoid skull base cysts and had either ophthalmological abnormalities (abnormal visual, ocular motor functions and/or abnormal blood supply to the eye) or an involvement of the cranial nerves (CN; i.e., the ophthalmic, ocular motor, trigeminal, abducens and/or facial nerves). The surgical strategy was to aim for total tumor removal in order to prevent the development of postoperative meningitis and reduce the risk of tumor recurrence. Cranial nerve manipulations were performed under the highest available microscope magnification and with the use of endoscope imaging. In addition, intraoperative monitoring of the relevant cranial nerves was performed. All surgical procedures were video recorded. Long-term outcomes of surgery were determined either by outpatient examination or via a phone call using a standard checklist. Results: Total removal was achieved in 7 patients (33.3%), near total removal in 2 patients (9.5%), and subtotal removal in 12 patients (57.2%). Ocular motor functions were normal after surgery in 11 patients (52.4%). In addition, abnormalities in the early postoperative period were observed in 10 patients (47.6%), but the functions subsequently normalized in 3 patients and improved but not normalized in 7 patients. All the three patients with trigeminal neuralgia showed regression of pain syndrome. Conclusion: We determined the ophthalmological abnormalities that had been present before and after surgery, and the time required for function recovery. We found that endoscopic-assisted radical removal of the epidermoid cyst under the highest available microscope magnification with intraoperative cranial nerve monitoring was safe and effective for preserving cranial nerve functions in the late time points after surgery.